Facial Profile of Young Indian Women from Maharashtra-A Cross-Sectional Pilot Study - Om N. Baghele; Anusha A. Math (Indian Journal of Dental Research)
Context: The anthropometric facial clinical proportions are used in the field of orthodontics, maxillofacial and plastic surgery for aesthetic or abnormality corrections. There is lack of enough literature on the facial profiles of Indians. Aim: To assess correlations between facial parameters and stature of young Maharashtrian women by using anthropometry. Settings and Design: It is a cross-sectional observational pilot study at Maharashtra Institute of Dental Sciences & Research, after approval from the Institutional Ethical Committee. Methods and Material: The study included 15 students of 21–23 years age selected by simple randomisation. The facial parameters were measured by sliding vernier calipers after identifying facial landmarks by stickers. Facial height (FH) in thirds; upper FH (UFH), middle FH (MFH) and lower FH (LFH); facial width (FW) and stature or overall height (OH) were calculated to define average facial features. Statistical Analysis: Multiple pairwise statistics and simple linear regression analyses were done for various dependent variables. Results: The means of UFH, MFH, LFH and total facial heights (TFH) were found to be 5.2 ± 0.54, 5.35 ± 0.34, 5.16 ± 0.44 and 15.7 ± 0.98 cm, respectively. The TFH showed a moderate correlation with stature (P ≤ 0.05, r = 0.64) and a strong correlation with lower lip length (P = 0.001, r = 0.78). Facial width showed a negative correlation with facial shape (P ≤ 0.05). Conclusions: The selected sample showed the statistically insignificant difference between UFH, MFH and LFH indicating equitable distribution among Indian women of Maharashtrian origin of 21–23 year age group. Longer TFH is positively correlated with higher stature and longer lower lip length.